Trend Kejadian Hipertensi dan Pola Distribusi Kejadian Hipertensi dengan Penyakit Penyerta secara Epidemiologi di Indonesia - Rizqiya, Mala; Ningrum, Dina Nur Anggraini (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Non-communicable diseases such as hypertension and co-morbidities are a major threat to global health. Knowing the distribution and trend of the disease is one way to monitor the progress of the disease to reduce mortality and morbidity. Therefore, researchers want to know the trend and distribution of hypertension with its comorbidities epidemiologically. Methods: This research is a quantitative study with a nested case control study research design, using BPJS Health sample data for the 2019-2020 service year. The variables in this study were hypertension and comorbidities. The analysis used is univariate analysis and trend in the form of graphs. Results: The trend of hypertension disease shows fluctuating results. The distribution of the disease showed results: hypertension (50%), myalgia (20%), acute upper respiratory tract infection (23.7%), functional dyspepsia (17.5%), headache (11%), common cold (13.5%). %), gastritis and duodenitis (12.4%), type 2 diabetes mellitus (6.9%), gastroenteritis and colitis (7.5%), dorsalgia (6.4%), acute pharyngitis (7.4%). Conclusion: This shows that the development of hypertension cases during 2019-2020 showed fluctuating results. Meanwhile, the distribution of hypertension and other disease has a different percentage.